Pre-competition and training anxiety among athletes practising gymnastic disciplines - Basiaga-Pasternak, J.; Biskup, A. (Journal of Kinesiology and Exercise Sciences, 2020)
Introduction: The gymnastic disciplines abound in difficult and risky technical elements. Excessive anxiety is a factor which can have a destructive effect on the athlete both at the stage of motor learning, as well as when performing during competitions. Anxiety is a natural human emotion, but whether it has positive or negative influence on an individual`s performance clearly depends upon its level. Aim of the study: The study aimed to determine the level of anxiety (as state, cognitive anxiety and somatic anxiety) among male and female gymnasts in situations before starting competitions and before training when mastering new, difficult elements. The following research questions were formulated: • Does the level of anxiety in the participants during learning new elements differ from the level of anxiety before starting to compete? • Does the level of somatic anxiety in the gymnasts during learning new elements differ from the level of anxiety before starting to compete? • Does the level of cognitive anxiety in the gymnasts during learning new elements differ from the level of anxiety before starting to compete? • What is the level of trait anxiety characteristic of the participating gymnasts? Material and method: Twenty eight people were assessed (14 women and 14 men) who professionally practice gymnastic disciplines. The average age of respondents was 18 years. All subjects were competing at championship level and had been practicing their sport for a minimum of 10 years. The Spielberger`s self-evaluation questionnaire (State-Trait-Anxiety Inventory, STAI) and the Smith`s, Smoll`s, Schutz`s Reaction to Competing Questionnaire (The Sport Anxiety Scale, SAS), as adapted to Polish by Krawczynski, were used in the research. Results: By adopting the criterion of statistical difference p ? 0.05 it was proven that there are statistically significant differences between the level of anxiety before training and before competition: state anxiety (p=0.033), somatic anxiety (p=0.004), and cognitive anxiety - attentions disorders (p=0.011). When analysing the average values of the participants, it was noted that they are characterised by an average trait anxiety level. Conclusion: The participating athletes who train in gymnastic disciplines are characterised by an average level of trait anxiety. The gymnasts experience stronger anxiety before competition than during a demanding training session.